After what time interval are we justified to diagnose immune checkpoint inhibitor-mediated polymyalgia rheumatica? - Ciro Manzo; Marco Isetta (Reumatismo)
Dear Editor, the number of cases of cancer patients diagnosed as having immune checkpoint inhibitor-mediated polymyalgia rheumatica has been steadily rising in published reports. However, the lack of a validated scale or algorithm is still a relevant methodological limit in diagnosing this nosologic entity...